Spirometry And X-Ray Findings in Cases of Interstitial Lung Diseases - Gagiya, Ashok K; Patel, Ankur S; Bhagat, Gautam R; Bhadiyadra, Vipul R; Patel, Khusbu S; Patel, Pratik (National Journal of Community Medicine, 2012)
Background: There are very few studies are done on spirometry and X-ray findings in interstitial lung diseases (ILD) in India. Methods: Pulmonary function tests were performed on computerized spirometer, through Kit Microsystems in 30 patients of high resolution computed tomography (HRCT) proven interstitial lung diseases in tertiary care centre. Results: Majority were in age group 40-49 years (mean age-45.23 years) and 66.5% male patients. Restrictive pattern (96.57%) was present in majority patients in spirometry. Most of patients (60%) of ILD showed reticular-nodular in X-ray chest. Conclusion: Restrictive pattern were observed regardless of smoking status in ILDs. Availability of non-invasive investigations like HRCT chest has increased our early recognitions of ILDs. Reticular-nodular pattern in X-ray chest is very important for suspecting ILD.